Clinical and prognostic significance of Krüppel-like transcription factor 6 expression in 67 patients with cutaneous malignant melanoma in China - Zhang, Nan; Qiu, Li-Yun; Yang, Fei; Gao, Wei; Ma, Wei-Yuan; Zhang, Min (Polish Journal of Pathology, 2021)
Krüppel-like transcription factor 6 (KLF6) is a ubiquitous tumor suppressor gene involved in regulating cell growth, proliferation, differentiation and angiogenesis. The objective of the study was to investigate the clinical and prognostic significance of KLF6 expression in cutaneous malignant melanoma (CMM) patients. A total of CMM 67 patients were enrolled in this study. The specimens were evaluated by immunohistochemistry to detect KLF6. The positive KLF6 expression in CMM tissues was significantly lower than in normal skin tissues (p < 0.01).The presence of KLF6 in CMM was correlated with ulceration (p < 0.01), lymph node metastasis (p < 0.01) and clinical stage (p < 0.01). The overall 5-year survival rate of the 67 patients was 13.4%. The 5-year survival rate of patients with negative KLF6 expression was correlated with KLF6 expression (p < 0.01), ulceration (p < 0.01), lymph node metastasis (p < 0.01), clinical stage (p < 0.01) and operation type (p < 0.01). Ulceration and clinical staging were independent relevant factors. In conclusion, the presence of KLF6 in CMM was correlated with ulceration, lymph node metastasis, clinical stage and poor prognosis.